Oral amelanotic melanoma of the maxilla. - Nasrollah Saghravanian; Mahdi Pazouki; Maryam Zamanzadeh (Tehran University of Medical Sciences, 2014)
Amelanotic melanoma is a variant of malignant melanoma comprising 2% to 8% of all malignant melanomas. The amelanotic presentation of melanoma in the oral cavity is extremely rare and has been reported only occasionally in the literature. Moreover, the lack of melanin makes these tumors difficult to diagnose than that of pigmented lesions and the prognosis tends to be poorer. Herein, we report an amelanotic melanoma involving the oral mucosa of the maxilla in a 27 year-old male.